The healing self : a revolutionary new plan to supercharge your immunity and stay well for life - Chopra, Deepak; Tanzi, Rudolph E. (Harmony Books, 2018)
"Combining the best current medical knowledge with a new approach grounded in integrative medicine, Chopra and Tanzi offer a groundbreaking new model of healing and the healing system, one of the main mysteries in the mind-body connection"--